OBSERVATIONS ON CHANGES IN THE MAJOR PROTEIN NITROGEN FRACTION OF PRAWNS AND SARDINES DURING ICE STORAGE - DEVADASAN, K; NAIR, M. RAJENDRANATHAN (Fishery Technology, 2025)
Changes in the major protein nitrogen fractions viz; sarcosp1asmic, myofibrillar and stroma have been studied in two species ofprawns and in oil sardine held in ice storage. Myofibrillar proteinswere observed to get denatured at a rapid rate as determined by saltextractability method. The sarcoplasmic proteins were not denaturedto any considerable extent. With sardine however, the extraction ofmyofibrillar proteins was inhibited rather in the uniced conditionitself presumably owing to the presence of free fatty acids.